The Influence of Shopping Lifestyle and Promotion of Nivea Skincare Products On Consumer Buying Interest Through Tiktok Shop - Halli Azzahrotu Ajmal; Cellyndhita Nuranisa Susanto; Abdullah Kafabi; Rahmadi Rahmadi (PT. Publikasiku Academic Solution, 2024)
This study aims to investigate the influence of shopping lifestyle and also the promotion of Nivea skincare products on consumer buying interest through TikTok Shop media. Through a quantitative approach, data was collected from the number of respondents obtained were 100 with the balance of people in Cirebon Regency who were aged 18-40 years that at that age they could make a very wise decision and also for people in Cirebon Regency who were wearing Nivea products or were wearing Nivea products. Respondents' answers to a question set out on questionnaires that have been distributed to consumers who want Nivea products, measured by the Likert Scale . respondents who are active TikTok users and also have an interest in skincare products. Various dimensions of product promotion, including visibility, interactivity, content relevance, influencer engagement, as well as brand credibility, were measured as independent variables. Consumer buying interest was measured as the dependent variable in this study. The results of the study prove that visibility, interactivity, and also the involvement of influencers have a positive and significant influence on consumer buying interest. However, the relevance of the content as well as brand credibility does not have a significant influence on consumer buying interest. In addition, this study also found that moderate lifestyle shopping effects of product promotion on consumer buying interest, proving that consumers' shopping lifestyles affect the extent to which product promotion affects their buying interest. Thus, this study fills the existing literature gap by investigating the influence of shopping lifestyle and product promotion on consumer buying interest specifically through TikTok Shop media. The findings provide valuable insights for marketers in developing effective promotional strategies on social media platforms, particularly for brands in the skincare industry.